Current status of xenotransplantation research and the strategies for preventing xenograft rejection - Zhou, Qiao; Li, Ting; Wang, Kaiwen; Zhang, Qi; Geng, Zhuowen; Deng, Shaoping; Cheng, Chunming; Wang, Yi (Frontiers in Immunology, 2022)
Transplantation is often the last resort for end-stage organ failures, e.g., kidney, liver, heart, lung, and pancreas. The shortage of donor organs is the main limiting factor for successful transplantation in humans. Except living donations, other alternatives are needed, e.g., xenotransplantation of pig organs. However, immune rejection remains the major challenge to overcome in xenotransplantation. There are three different xenogeneic types of rejections, based on the responses and mechanisms involved. It includes hyperacute rejection (HAR), delayed xenograft rejection (DXR) and chronic rejection. In this review, we summarized recent progress in xenotransplantation research, and comprehensively discussed the mechanism of the immunological rejection and the strategies for preventing Xenograft rejection. Taken together, these information will benefit the current immunological research in the field of xenotransplantation.